Therapy of swallowing and speech problem in patients with progressive supranuclear palsy - Bunijevac Mila (Srpski Arhiv za Celokupno Lekarstvo)
Introduction. Progressive supranuclear palsy (PSP) is a rare form of neurodegenerative extrapyramidal disease. In addition to symmetrical parkinsonism, early falls, and non-reactivity to dopaminomimetic therapy, the disease also manifests as swallowing problems with frequent choking and incomprehensible, difficult speech. In this paper, we present a case of a patient with PSP who exhibited severe swallowing and speech disorders in the clinical presentation of the disease. Appropriate therapy was applied, resulting in a positive response with partial relief of the mentioned symptoms. Case outline. A 68-year-old male patient was referred to a speech therapist by a neurologist due to difficulties with swallowing and speaking. The patient exhibited impairments in the preparatory and oral phases of swallowing, including insufficient labial occlusion and weakened tongue mobility. The patient underwent intensive speech therapy treatment for six months. The rehabilitation program led to improved swallowing function and partial improvement in speech. Conclusion. The treatment of patients with PSP should be approached seriously and interdisciplinary, given the absence of causal therapy and the reliance on symptomatic treatment for specific disabling conditions. It is essential to focus on the selection of rehabilitation programs that can improve speech and swallowing functions, as well as enhance the quality of life for patients.